Interaksi Guru-Siswa Dalam Pembelajaran Bahasa Inggris di MTsN 2 Pademawu - Mohammad Amiruddin; M. Darrin Zuhri (KABILAH : Journal of Social Community, 2020)
Abstract:This research describes in details the teacher-student interactions in learning English together with the teachers’ ways and the role of their interaction in learning English. This study is a quantitative research by using descriptive case study approach. The participants of this study are students at MTsN 2 Pamekasan. Observation and interviews with the teachers and students were conducted to get the data of the teacher-student interactions. The results of the study demonstrate that restricted English interaction and full English interaction are two kinds of interactions used by the teachers and students in learning English at MTsN 2 Pamekasan. The roles of teacher-student interactions in learning English at MTsN 2 Pamekasan Pamekasan are the students have input to learn and to communicate in English as well as they are enthusiasm for interacting in English with their teachers. This study facilitates the teachers and students who are teaching and studying English in addition to work together; share the ideas and opinion in English. It helps students of MTsN 2 Pamekasan to have better English proficiency level. The more interactions are provided by the teachers, the more input the students have. Key words: interaction, teacher-student, learning English, input. Abstrak:Penelitian ini menjelaskan secara detail interaksi guru-siswa dalam pembelajaran bahasa Inggris dan peran dari interaksi tersebut dalam pembelajaran bahasa Inggris di MTsN 2 Pamekasan. Penelitian ini adalah penelitian kualitatif dengan menggunakan pendekatan descriptive case study. Participants dalam penelitian ini adalah siswa di MTsN 2 Pamekasan. Observasi dan interview dilakukan untuk memperoleh data interaksi guru siswa. Hasil penelitian ini menunjukkan bahwa terdapat dua bentuk interaksi yang dilakukan guru dan siswa di MTsN 2 Pamekasan yaitu restricted English interaction dan full English interaction. Interaksi guru-siswa dalam di MTsN 2 Pamekasan dapat memberikan input dalam pembelajaran bahasa Inggris dan dapat motivasi siswa berinteraksi menggunakan bahasa Inggris. Temuan ini bermanfaat bagi guru dan siswa yang sedang mengajar dan belajar bahasa Inggris. Juga membantu mereka untuk berinteraksi, bertukar pikira, ide, dan gagasan dengan bahasa Inggris. Hal ini membantu siswa untuk memiliki kecakapan berbahasa Inggris. Semakin sering guru memberikan kesempatan berinteraksi dengan mereka menggunakan bahasa Inggris, semakin banyak input yang mereka peroleh.Kata Kunci: interaksi, guru-siswa, pembelajaran bahasa Inggris, input